2000
DOI: 10.1128/.68.11.6384-6390.2000
|View full text |Cite
|
Sign up to set email alerts
|

Role of Streptolysin O in a Mouse Model of Invasive Group A Streptococcal Disease

Abstract: Many of the virulence factors that have been characterized for group A streptococci (GAS) are not expressed in all clinical isolates. One putative virulence factor that is present among most is streptolysin O (Slo), a protein with well-characterized cytolytic activity for many eukaryotic cells types. In other bacterial pathogens, proteins homologous to Slo have been shown to be essential for virulence, but the role of Slo in GAS had not been previously examined. To investigate the role of Slo in GAS virulence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…The method of Bunce et al . (1992) as modified by others (Schrager et al ., 1996; Limbago et al ., 2000) was used to establish an infection of S. pyogenes in the subcutaneous tissue of mice as described in detail elsewhere (Brenot et al ., 2004). To analyse bacterial transcript levels, tissues were excised from each animal to include the dermis and underlying soft tissue of the lesion.…”
Section: Methodsmentioning
confidence: 99%
“…The method of Bunce et al . (1992) as modified by others (Schrager et al ., 1996; Limbago et al ., 2000) was used to establish an infection of S. pyogenes in the subcutaneous tissue of mice as described in detail elsewhere (Brenot et al ., 2004). To analyse bacterial transcript levels, tissues were excised from each animal to include the dermis and underlying soft tissue of the lesion.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to these in vitro studies, the contribution of SLS and SLO to S. pyogenes virulence has been examined in murine experimental models of infection. Thus, Limbago and co-workers reported that an SLO-deficient S. pyogenes mutant strain was significantly more attenuated than the isogenic parental microorganisms after subcutaneous injection in mice (Limbago et al, 2000). Likewise, a SLS-deficient S. pyogenes was found more attenuated than the parental strains in the production of necrotic lesions in a murine model of dermonecrosis (Betschel et al, 1998).…”
Section: Introductionmentioning
confidence: 98%
“…In a murine model of cutaneous infection, GAS strains lacking SLS activity were less virulent than the wild-type (WT) isogenic parental strain (Betschel et al, 1998;Mitchell et al, 2009). Soft tissue damage in mice associated with bacterial proliferation, inflammation, vascular injury and formation of necrotic lesions also depends on the activity of SLS in GAS, group G Streptococcus (GGS) and Streptococcus iniae (Betschel et al, 1998;Limbago et al, 2000;Fuller et al, (Sierig et al, 2003;Miyoshi-Akiyama et al, 2005;Lin et al, 2009) Streptococcus dysgalactiae ssp. equisimilis ND (Humar et al, 2002;Hashikawa et al, 2004) Streptococcus equi ssp.…”
Section: Streptolysin Smentioning
confidence: 99%
“…In subcutaneous, intravenous and intraperitoneal murine models of invasive disease, slo-deficient GAS mutants have decreased virulence compared with WT parental strains (Limbago et al, 2000;Ato et al, 2008;Timmer et al, 2009). A recent study showed that SLO binding to A549 epithelial cells does not require cholesterol, suggesting that cholesterol is not the membrane receptor for SLO (Mozola et al, 2014).…”
Section: Streptolysin Omentioning
confidence: 99%